2010
DOI: 10.1038/nature08746
|View full text |Cite
|
Sign up to set email alerts
|

TCR–peptide–MHC interactions in situ show accelerated kinetics and increased affinity

Abstract: The recognition of foreign antigens by T lymphocytes is essential to most adaptive immune responses. It is driven by specific T-cell antigen receptors (TCRs) binding to antigenic peptidemajor histocompatibility complex (pMHC) molecules on other cells1. If productive, these interactions promote the formation of an immunological synapse2,3. Here we show that synaptic TCR-pMHC binding dynamics differ significantly from TCR-pMHC binding in solution. We used single-molecule microscopy and fluorescence resonance ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
679
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 453 publications
(721 citation statements)
references
References 30 publications
38
679
2
2
Order By: Relevance
“…Interestingly, this remarkable probing activity has not been seen in fluorescence studies of T cell-APC interactions, perhaps because of a lack of resolution and/or its rapidity. Furthermore, one cannot see this phenomenon when artificial bilayers on glass slides are used as APCs, but it may be reflected in the pericentric actin polymerization seen in those systems (34), which also destabilizes TCR binding to peptide-MHC (35).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this remarkable probing activity has not been seen in fluorescence studies of T cell-APC interactions, perhaps because of a lack of resolution and/or its rapidity. Furthermore, one cannot see this phenomenon when artificial bilayers on glass slides are used as APCs, but it may be reflected in the pericentric actin polymerization seen in those systems (34), which also destabilizes TCR binding to peptide-MHC (35).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, during the lifetime of the TCR-pMHC bond a coreceptor would disengage from the MHC ≈1,000 times, making it implausible that stabilization of TCR-pMHC interactions would be achieved. Recent data measuring TCR binding within a synapse (9) show that it is less stable, perhaps 1,000 ms for an average TCR-ligand interaction due to actin polymerization activity, but this is still far in excess of what has been reported for CD4 and CD8 interactions.…”
mentioning
confidence: 85%
“…It has been suggested that CD4 stabilizes the molecular complex of TCR and peptide-MHC (pMHC) by binding to the same MHC either simultaneously with the TCR (7) or shortly after TCR-pMHC engagement (2,3). However, from more recent 2D measurements, CD4 blockades showed no effect on the stability of TCR binding to agonist peptide-MHC complexes in a synapse (8). In terms of signal transduction, the role of CD4 has been studied based on the binding ability of a cysteine motif in the cytoplasmic tail of CD4 to Src kinase p56lck (Lck) (9), which is responsible for the phosphorylation of the immunoreceptor tyrosine-based activation motif (ITAM) sequences in TCR-CD3 complex as the earliest observable biochemical event during T-cell activation (10).…”
mentioning
confidence: 94%